Comparison of Single Layer Interrupted Extramucosal Anastomsis with Double Layer Continuous Anastomosis Among Patients with Benign Small Intestinal Pathology - MUHAMMAD KAREEMULLAH, ASIF HANIF, MUHAMMAD SHABBIR AHMAD, ZAHID SATTAR, (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare outcome of single layer interrupted extramucosal anastomsis with double layer continuous anastomosis among patients with benign small intestinal pathology such as perforation, tuberculosis, trauma or typhoid. Methodology: This prospective randomized controlled trial was conducted at Surgical floor LGH/PGMI. The study was completed in six months using non-probability consecutive sampling. Two hundred patients with benign intestinal pathology requiring intestinal anastomosis were divided in two groups, 100 patients in each group were taken in group A patients were managed with single layer extramucosal interrupted anastomosis and in group B patients were treated with underwent double layer continuous anastomosis. Variable like leakage was described by frequency distribution table, Chi-square test was applied as a test for significance & p-value ≤ 0.05 was considered significant. Results: Five (5%) patients in group A had leakage detected on seventh day, while 15 (15%) patients in group B had leakage detected on seventh day. No leakage was seen among 95 (95%) and 85 (85%) patient in group A and B, respectively. (p = 0.018) Conclusions: Less leakage occurred with single layer anastomosis as compared with double layer anastomosis. Hence we recommend that single layer anastomosis should be adopted for patients with benign intestinal intestinal pathologies.